Incidence of and risk factors for incisional hernia after abdominal surgery. Issue 11 (14th August 2014) - Itatsu, K.; Yokoyama, Y.; Sugawara, G.; Kubota, H.; Tojima, Y.; Kurumiya, Y.; Kono, H.; Yamamoto, H.; Ando, M.; Nagino, M.
<x xml:space="preserve">Abstract</x> Background Few larger studies have estimated the incidence of incisional hernia (IH) after abdominal surgery. Methods Patients who had abdominal surgery between November 2009 and February 2011 were included in the study. The incidence rate and risk factors for IH were monitored for at least 180 days. Results A total of 4305 consecutive patients were registered. Of these, 378 were excluded because of failure to complete follow‐up and 3927 patients were analysed. IH was diagnosed in 318 patients. The estimated incidence rates for IH were 5·2 per cent at 12 months and 10·3 per cent at 24 months. In multivariable analysis, wound classification III and IV (hazard ratio (HR) 2·26, 95 per cent confidence interval 1·52 to 3·35), body mass index of 25 kg/m2 or higher (HR 1·76, 1·35 to 2·30), midline incision (HR 1·74, 1·28 to 2·38), incisional surgical‐site infection (I‐SSI) (HR 1·68, 1·24 to 2·28), preoperative chemotherapy (HR 1·61, 1·08 to 2·37), blood transfusion (HR 1·46, 1·04 to 2·05), increasing age by 10‐year interval (HR 1·30, 1·16 to 1·45), female sex (HR 1·26, 1·01 to 1·59) and thickness of subcutaneous tissue for every 1‐cm increase (HR 1·18, 1·03 to 1·35) were identified as independent risk factors. Compared with superficial I‐SSI, deep I‐SSI was more strongly associated with the development of IH. Conclusion Although there are several risk factors for IH, reducing I‐SSI is an important step in the prevention of IH. Registration number: UMIN000004723 (University Hospital Medical Information Network, http://www.umin.ac.jp/ctr/index.htm).